Mini Open Spinous Process Splitting Laminectomy in the management of Cervical Spondylotic Myelopathy - Hatem Hamdy (Egyptian Spine Association, 2017)
Background Data: Muscle dissection associated with posterior approach to cervical spine usually results in local pain, muscle wasting and temporarily restricted neck movement. Use of muscle sparing spinous process splitting approach for cervical laminectomy allows decompression of the spinal cord and neural foramen if needed. Meanwhile, it does not require instrumentation, fusion and it preserves cervical spine stability. Purpose: To assess the effectiveness of spinous process splitting approach for cervical laminectomy in cervical spondylotic myelopathy. Study Design: Prospective clinical case study. Patients and Methods: Patient Sample: Fifteen patients with cervical spondylotic myelopathy, eleven males and 4 females with mean age 66.4±6.6 (Range 44-71) years. All patients underwent muscle sparing spinous process splitting cervical laminectomy. Outcome Measures: Operative time and blood loss were recorded. Clinical outcome was assessed by the JOA score and VAS. MRI was done 6 months postoperative to assess decompression. Spinal stability and curvature index were assessed on plain cervical radiographs. Results: No case of wound dehiscence was recorded. There was significant improvement of JOA scores and brachialgia and neck pain VAS scores at 6 months, the mean JOA recovery rate was 56.2%. No patient had postoperative kyphosis or instability and 66.6% of patients had improved modified Ishihara cervical curvature index. No neurological deterioration was recorded in the follow-up. No patient had newly developed axial pain. MRI revealed adequate decompression of the spinal cord in all patients. Conclusion: The spinous process splitting cervical laminectomy allows good spinal cord decompression and preserves spine curvature and stability. The mini open approach and preservation of interspinous ligaments could play a role in wound dehiscence prevention. (2017ESJ133)